Inorganic near-infrared fluorescent material as well as preparation method and application thereof
By preparing inorganic near-infrared fluorescent materials with the chemical formula Mg(CrM)xTi1-xO3, the problems of narrow luminescence spectrum and limited application of existing materials are solved, and wide emission bands and high photoluminescence quantum yields are achieved, which are suitable for near-infrared imaging and other fields.
Patent Information
- Application Number
- CN202410836780.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-26
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-06-26
AI Technical Summary
The luminescence spectrum of existing inorganic near-infrared fluorescent materials is narrow, and the luminescence peak range is less than 850 nm, limiting their application in the field of imaging.
An inorganic near-infrared fluorescent material is provided, with the chemical formula of Mg(CrM)xTi1-xO3, 0
The material exhibits excellent near-infrared luminescence performance under ultraviolet-visible light excitation, with a wide emission band range (750-1200 nm), a peak position at 866 nm, and a photoluminescence quantum yield of 31.55%, meeting commercial standards and is suitable for fields such as near-infrared imaging.
Smart Images

Figure CN119529833A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of luminescent materials, and particularly to an inorganic near-infrared fluorescent material, a preparation method thereof, and an application thereof. Background Art
[0002] Near-infrared fluorescent materials can absorb ultraviolet or visible light and convert it into near-infrared photons with lower energy, and have important applications in many fields such as food detection, night vision, non-destructive detection, and biomedical imaging.
[0003] Traditional inorganic near-infrared fluorescent materials can be divided into two categories: rare-earth ion-doped fluorescent materials and transition-metal ion-doped fluorescent materials. Rare-earth ion-doped fluorescent materials mostly use Nb 3+ and Yb 3+ as the luminescence center. The excitation efficiency of rare-earth ions is low, and the emission spectrum is relatively narrow; most transition-metal ion-doped fluorescent materials use Cr 3+ as the luminescence center, and the emission peaks mostly concentrate in the range of 750-850 nm, thus limiting their applications in the imaging field.
[0004] Therefore, the existing technology still needs to be improved and developed. Summary of the Invention
[0005] Based on the above deficiencies of the existing technology, the purpose of the present invention is to provide an inorganic near-infrared fluorescent material, a preparation method thereof, and an application thereof, aiming to solve the problems that the existing inorganic near-infrared fluorescent materials have a narrow emission spectrum, the emission peak range is less than 850 nm, and their applications in the imaging field are limited.
[0006] The technical solution of the present invention is as follows:
[0007] In the first aspect of the present invention, an inorganic near-infrared fluorescent material is provided, wherein the chemical formula of the inorganic near-infrared fluorescent material is Mg(CrM) x Ti 1-x O3; wherein, 0 < x ≤ 0.06, and M is at least one alkali metal.
[0008] Optionally, M is at least one of Li, Na, and K.
[0009] In the second aspect of the present invention, a preparation method of the inorganic near-infrared fluorescent material as described above in the present invention is provided, wherein the method includes the following steps:
[0010] According to Mg(CrM) x Ti 1-xThe stoichiometric ratio of each element in O3 is obtained by mixing a magnesium source, a titanium source, a chromium source and an excess of at least one alkali metal source, sintering at a first preset temperature for a first preset time, and then sintering at a second preset temperature for a second preset time to obtain the inorganic near-infrared fluorescent material.
[0011] Optionally, the preparation method of the inorganic near-infrared fluorescent material specifically comprises the following steps:
[0012] According to Mg(CrM) x Ti 1-x The magnesium source, the titanium source, the chromium source and an excess of at least one alkali metal source are mixed in a stoichiometric ratio of each element in O3, and then subjected to a first grinding to obtain a first mixture;
[0013] sintering the first mixture at a first preset temperature for a first preset time, and then grinding it for a second time to obtain a second mixture;
[0014] The second mixture is sintered at a second preset temperature for a second preset time to obtain the inorganic near-infrared fluorescent material.
[0015] Optionally, ethanol is added during the first grinding process, and the first grinding time is 15 to 30 minutes. Ethanol is added during the second grinding process, and the second grinding time is 15 to 30 minutes.
[0016] Optionally, the magnesium source includes magnesium oxide; the titanium source includes titanium dioxide; and the chromium source includes chromium trioxide.
[0017] Optionally, the alkali metal source comprises lithium carbonate, sodium carbonate or potassium carbonate.
[0018] Optionally, the first preset temperature is 900° C., and the first preset time is 3 hours.
[0019] Optionally, the second preset temperature is 1300° C., and the second preset time is 2 hours.
[0020] The third aspect of the present invention provides an inorganic near-infrared fluorescent material as described above, or an inorganic near-infrared fluorescent material prepared by the preparation method as described above in the field of near-infrared imaging.
[0021] Beneficial effects: The inorganic near-infrared fluorescent material provided by the present invention has excellent near-infrared luminescence performance under ultraviolet-visible light excitation, a wide emission band range (750-1200nm), a peak position at 866nm, and a photoluminescence quantum yield of 31.55%, which meets commercial standards and can be applied to near-infrared imaging and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is the crystal structure diagram of the inorganic near-infrared fluorescent material prepared in Example 3.
[0023] Figure 2 It is the XRD pattern of the inorganic near-infrared fluorescent material prepared in Example 3.
[0024] Figure 3 It is the element distribution diagram of the inorganic near-infrared fluorescent material prepared in Example 3.
[0025] Figure 4 It is the XPS pattern of the inorganic near-infrared fluorescent material prepared in Example 3.
[0026] Figure 5 It is the fluorescence excitation spectrum diagram of the inorganic near-infrared fluorescent materials prepared in Example 3, Example 7, Example 8 and Comparative Example 1.
[0027] Figure 6 It is the fluorescence emission spectrum diagram of the inorganic near-infrared fluorescent materials prepared in Example 3 and Comparative Example 1 under the excitation wavelength of 315 nm.
[0028] Figure 7 It is the fluorescence emission spectrum diagram for testing the inorganic near-infrared fluorescent materials prepared in Example 3 and Comparative Example 1 under the excitation wavelength of 728 nm. Detailed implementation manners
[0029] The present invention provides an inorganic near-infrared fluorescent material, its preparation method and application. To make the purpose, technical solution and effect of the present invention clearer and more definite, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0030] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as commonly understood by those skilled in the technical field to which the present invention belongs. The terms used in the specification of the present invention herein are only for the purpose of describing specific implementation manners and are not intended to limit the present invention.
[0031] An embodiment of the present invention provides an inorganic near-infrared fluorescent material, wherein the chemical formula of the inorganic near-infrared fluorescent material is Mg(CrM) x Ti 1-x O3; wherein, 0 < x ≤ 0.06, and M is at least one alkali metal.
[0032] The inorganic near-infrared fluorescent material provided by the embodiment of the present invention has excellent near-infrared luminescence performance under the excitation of ultraviolet-visible light (315nm, 514nm, 728nm), a wide emission band range (750-1200nm), a peak position at 866nm, and a photoluminescence quantum yield of 31.55%, which meets commercial standards and can be applied to fields such as near-infrared imaging.
[0033] In this embodiment, the chemical formula of the inorganic near-infrared fluorescent material is Mg(CrM): x Ti 1-x O3 is also MgCr x M x Ti 1-x O3, abbreviated as MgTiO3:Cr 3+ ,M + For example, when M is Na, the inorganic near-infrared fluorescent material can be represented by MgTiO3:Cr 3+ ,Na + .
[0034] In some embodiments, M is at least one of Li, Na, and K. For example, the chemical formula of the inorganic near-infrared fluorescent material is Mg(CrLi): x Ti 1-x O3、Mg(CrNa) x Ti 1-x O3、Mg(CrK) x Ti 1-x O3、Mg(CrLi 0.5 Na 0.5 ) x Ti 1-x O3, etc.
[0035] The embodiment of the present invention further provides a method for preparing the inorganic near-infrared fluorescent material of the present invention as described above, wherein the method comprises the following steps:
[0036] According to Mg(CrM) x Ti 1-x The stoichiometric ratio of each element in O3 is obtained by mixing a magnesium source, a titanium source, a chromium source and an excess of at least one alkali metal source, sintering at a first preset temperature for a first preset time, and then sintering at a second preset temperature for a second preset time to obtain the inorganic near-infrared fluorescent material.
[0037] The preparation method provided by the embodiment of the present invention is simple and low in cost. The raw materials used in the preparation method can all be commercially available and low-cost raw materials. The prepared inorganic near-infrared fluorescent material has the characteristics of good thermal stability, excellent near-infrared luminescence performance under ultraviolet-visible light (315nm, 514nm, 728nm) excitation, a wide emission band range, a peak position at 866nm, and a photoluminescence quantum yield of 31.55%, which meets commercial standards and can be applied to near-infrared imaging and other fields.
[0038] In the embodiment of the present invention, magnesium source and titanium source are used as matrix components, chromium source and alkali metal source are used as doping ion components, and during the sintering process, chromium ions and alkali metal ions replace titanium ions and are doped into MgTiO3.
[0039] In the embodiment of the present invention, the alkali metal acts as a flux on the one hand and plays a role of charge supplement on the other hand. Specifically, Cr 3+ Replace Ti 4+ This is an alivalent substitution. If alkali metal is not added, defects will be generated, thereby affecting the luminous efficiency and thermal stability. Therefore, in the embodiment of the present invention, alkali metal is added to compensate for the charge and maintain the valence balance.
[0040] Taking M as Na as an example, the charge compensation process is: Cr 3+ +Na + →Ti 4+ That is to say, in this process, a Cr 3+ With a Na + Replace a Ti together 4+ .
[0041] In some embodiments, the method for preparing the inorganic near-infrared fluorescent material specifically comprises the following steps:
[0042] According to Mg(CrM) x Ti 1-x The magnesium source, the titanium source, the chromium source and an excess of at least one alkali metal source (the at least one alkali metal source is additionally added to 3% to 5% of the total mass of the magnesium source, the titanium source and the chromium source) are mixed according to the stoichiometric ratio of each element in O3, and then ground for the first time to obtain a first mixture;
[0043] sintering the first mixture at a first preset temperature for a first preset time, and then grinding it for a second time to obtain a second mixture;
[0044] The second mixture is sintered at a second preset temperature for a second preset time to obtain the inorganic near-infrared fluorescent material.
[0045] In this embodiment, the alkali metal source is excessive, that is, it can be understood that according to Mg(CrM) x Ti1-x The stoichiometric ratio of each element in O3 is to mix the magnesium source, titanium source, chromium source and at least one alkali metal source, and then add 3% to 5% of the total mass of the magnesium source, titanium source and chromium source.
[0046] In some embodiments, ethanol is added during the first grinding process, and the time of the first grinding is 15 to 30 minutes. Ethanol is added during the second grinding process, and the time of the second grinding is 15 to 30 minutes.
[0047] In some embodiments, the magnesium source comprises magnesium oxide; the titanium source comprises titanium dioxide; and the chromium source comprises at least one of chromium oxide.
[0048] In some embodiments, the alkali metal source comprises lithium carbonate, sodium carbonate, or potassium carbonate.
[0049] In some embodiments, the first preset temperature is 900° C., and the first preset time is 3 hours.
[0050] In some embodiments, the second preset temperature is 1300° C., and the second preset time is 2 hours.
[0051] The embodiment of the present invention also provides an inorganic near-infrared fluorescent material as described above in the embodiment of the present invention, or an inorganic near-infrared fluorescent material prepared by the preparation method as described above in the embodiment of the present invention, and its application in the field of near-infrared imaging. The inorganic near-infrared fluorescent material has the characteristics of good thermal stability, excellent near-infrared luminescence performance under the excitation of ultraviolet-visible light (315nm, 514nm, 728nm), a wide emission band range, a peak position at 866nm, and a photoluminescence quantum yield of 31.55%, which meets the commercial standard, and therefore can be applied to fields such as near-infrared imaging.
[0052] Different materials have different degrees of absorption of near-infrared light at different locations due to their uneven density, thickness and material distribution. Correspondingly, the degree of attenuation of near-infrared light after penetrating an object is different. This principle can be used to record the difference (distribution state) of infrared energy reflected or radiated by a scene or different parts of the scene, and convert it into a two-dimensional visible image in a certain way, which is called near-infrared imaging. When the projection thickness is constant, the dark area in the image indicates that the area has a strong absorption of near-infrared light; conversely, the bright area in the image indicates that the area has a weak absorption of near-infrared light. Observers can judge the properties of the object by combining the image with factors such as the density and thickness of the object.
[0053] Specifically, the inorganic near-infrared fluorescent material can be applied to food detection, night vision, plant growth, non-destructive detection, biomedical imaging, etc. In addition, the inorganic near-infrared fluorescent material can form a clear image under visible light excitation and can be used to prepare a fluorescence conversion light-emitting diode.
[0054] The present invention will be further described below by means of specific examples.
[0055] Unless otherwise specified, all raw materials and equipment used in the following examples are commercially available products.
[0056] Example 1
[0057] This embodiment provides a method for preparing an inorganic near-infrared fluorescent material, comprising the following steps:
[0058] According to Mg(CrNa) 0.002 Ti 0.998 The stoichiometric ratio of each element in O3 is added into an agate mortar by adding magnesium oxide, titanium dioxide, chromium trioxide and excess sodium carbonate (sodium carbonate is added 3% of the total mass of magnesium oxide, titanium dioxide and chromium trioxide), and then adding an appropriate amount of anhydrous ethanol and grinding for 30 minutes to obtain a first mixture;
[0059] The first mixture was transferred into a corundum crucible and placed into a muffle furnace for pre-calcination at 900° C. for 3 hours. After cooling to room temperature, an appropriate amount of anhydrous ethanol was added to the pre-calcined product and ground for 30 minutes to obtain a second mixture.
[0060] The second mixture is placed in a muffle furnace and sintered at 1300° C. for 2 hours (i.e., secondary sintering), and after cooling to room temperature, the inorganic near-infrared fluorescent material Mg(CrNa) is obtained. 0.002 Ti 0.998 O3, which is in powder state.
[0061] Example 2
[0062] This embodiment provides a method for preparing an inorganic near-infrared fluorescent material, comprising the following steps:
[0063] According to Mg(CrNa) 0.005 Ti 0.995 The stoichiometric ratio of each element in O3 is added into an agate mortar by adding magnesium oxide, titanium dioxide, chromium trioxide and excess sodium carbonate (sodium carbonate is added 3% of the total mass of magnesium oxide, titanium dioxide and chromium trioxide), and then adding an appropriate amount of anhydrous ethanol and grinding for 30 minutes to obtain a first mixture;
[0064] The first mixture was transferred into a corundum crucible and placed into a muffle furnace for pre-calcination at 900° C. for 3 hours. After cooling to room temperature, an appropriate amount of anhydrous ethanol was added to the pre-calcined product and ground for 30 minutes to obtain a second mixture.
[0065] The second mixture is placed in a muffle furnace and sintered at 1300° C. for 2 hours (i.e., secondary sintering), and after cooling to room temperature, the inorganic near-infrared fluorescent material Mg(CrNa) is obtained. 0.005 Ti 0.995 O3, which is in powder state.
[0066] Example 3
[0067] This embodiment provides a method for preparing an inorganic near-infrared fluorescent material, comprising the following steps:
[0068] According to Mg(CrNa) 0.01 Ti 0.99 The stoichiometric ratio of each element in O3 is added into an agate mortar by adding magnesium oxide, titanium dioxide, chromium trioxide and excess sodium carbonate (sodium carbonate is added 3% of the total mass of magnesium oxide, titanium dioxide and chromium trioxide), and then adding an appropriate amount of anhydrous ethanol and grinding for 30 minutes to obtain a first mixture;
[0069] The first mixture was transferred into a corundum crucible and placed into a muffle furnace for pre-calcination at 900° C. for 3 hours. After cooling to room temperature, an appropriate amount of anhydrous ethanol was added to the pre-calcined product and ground for 30 minutes to obtain a second mixture.
[0070] The second mixture is placed in a muffle furnace and sintered at 1300° C. for 2 hours (i.e., secondary sintering), and after cooling to room temperature, the inorganic near-infrared fluorescent material Mg(CrNa) is obtained. 0.01 Ti 0.99 O3, which is in powder state.
[0071] Example 4
[0072] This embodiment provides a method for preparing an inorganic near-infrared fluorescent material, comprising the following steps:
[0073] According to Mg(CrNa) 0.02 Ti 0.98 The stoichiometric ratio of each element in O3 is added into an agate mortar by adding magnesium oxide, titanium dioxide, chromium trioxide and excess sodium carbonate (sodium carbonate is added 3% of the total mass of magnesium oxide, titanium dioxide and chromium trioxide), and then adding an appropriate amount of anhydrous ethanol and grinding for 30 minutes to obtain a first mixture;
[0074] The first mixture was transferred into a corundum crucible and placed into a muffle furnace for pre-calcination at 900° C. for 3 hours. After cooling to room temperature, an appropriate amount of anhydrous ethanol was added to the pre-calcined product and ground for 30 minutes to obtain a second mixture.
[0075] The second mixture is placed in a muffle furnace and sintered at 1300° C. for 2 hours (i.e., secondary sintering), and after cooling to room temperature, the inorganic near-infrared fluorescent material Mg(CrNa) is obtained. 0.02 Ti 0.98 O3, which is in powder state.
[0076] Example 5
[0077] This embodiment provides a method for preparing an inorganic near-infrared fluorescent material, comprising the following steps:
[0078] According to Mg(CrNa) 0.04 Ti 0.96 The stoichiometric ratio of each element in O3 is added into an agate mortar by adding magnesium oxide, titanium dioxide, chromium trioxide and excess sodium carbonate (sodium carbonate is added 3% of the total mass of magnesium oxide, titanium dioxide and chromium trioxide), and then adding an appropriate amount of anhydrous ethanol and grinding for 30 minutes to obtain a first mixture;
[0079] The first mixture was transferred into a corundum crucible and placed into a muffle furnace for pre-calcination at 900° C. for 3 hours. After cooling to room temperature, an appropriate amount of anhydrous ethanol was added to the pre-calcined product and ground for 30 minutes to obtain a second mixture.
[0080] The second mixture is placed in a muffle furnace and sintered at 1300° C. for 2 hours (i.e., secondary sintering), and after cooling to room temperature, the inorganic near-infrared fluorescent material Mg(CrNa) is obtained. 0.04 Ti 0.96 O3, which is in powder state.
[0081] Example 6
[0082] This embodiment provides a method for preparing an inorganic near-infrared fluorescent material, comprising the following steps:
[0083] According to Mg(CrNa) 0.06 Ti 0.94 The stoichiometric ratio of each element in O3 is added into an agate mortar by adding magnesium oxide, titanium dioxide, chromium trioxide and excess sodium carbonate (sodium carbonate is added 3% of the total mass of magnesium oxide, titanium dioxide and chromium trioxide), and then adding an appropriate amount of anhydrous ethanol and grinding for 30 minutes to obtain a first mixture;
[0084] The first mixture was transferred into a corundum crucible and placed into a muffle furnace for pre-calcination at 900° C. for 3 hours. After cooling to room temperature, an appropriate amount of anhydrous ethanol was added to the pre-calcined product and ground for 30 minutes to obtain a second mixture.
[0085] The second mixture is placed in a muffle furnace and sintered at 1300° C. for 2 hours (i.e., secondary sintering), and after cooling to room temperature, the inorganic near-infrared fluorescent material Mg(CrNa) is obtained. 0.06 Ti 0.94 O3, which is in powder state.
[0086] Example 7
[0087] This embodiment provides a method for preparing an inorganic near-infrared fluorescent material, comprising the following steps:
[0088] According to Mg(CrLi) 0.01 Ti 0.99 According to the stoichiometric ratio of each element in O3, magnesium oxide, titanium dioxide, chromium trioxide and excess lithium carbonate (lithium carbonate is added to an additional 3% of the total mass of magnesium oxide, titanium dioxide and chromium trioxide) are added to an agate mortar, and then an appropriate amount of anhydrous ethanol is added and ground for 30 minutes to obtain a first mixture;
[0089] The first mixture was transferred into a corundum crucible and placed into a muffle furnace for pre-calcination at 900° C. for 3 hours. After cooling to room temperature, an appropriate amount of anhydrous ethanol was added to the pre-calcined product and ground for 30 minutes to obtain a second mixture.
[0090] The second mixture is placed in a muffle furnace and sintered at 1300° C. for 2 hours (i.e., secondary sintering), and after cooling to room temperature, the inorganic near-infrared fluorescent material Mg(CrLi) is obtained. 0.01 Ti 0.99 O3, which is in powder state.
[0091] Example 8
[0092] This embodiment provides a method for preparing an inorganic near-infrared fluorescent material, comprising the following steps:
[0093] According to Mg(CrK) 0.01 Ti 0.99 According to the stoichiometric ratio of each element in O3, magnesium oxide, titanium dioxide, chromium trioxide and excess potassium carbonate (potassium carbonate is added to an additional 3% of the total mass of magnesium oxide, titanium dioxide and chromium trioxide) are added to an agate mortar, and then an appropriate amount of anhydrous ethanol is added and ground for 30 minutes to obtain a first mixture;
[0094] The first mixture was transferred into a corundum crucible and placed into a muffle furnace for pre-calcination at 900° C. for 3 hours. After cooling to room temperature, an appropriate amount of anhydrous ethanol was added to the pre-calcined product and ground for 30 minutes to obtain a second mixture.
[0095] The second mixture is placed in a muffle furnace and sintered at 1300° C. for 2 hours (i.e., secondary sintering), and after cooling to room temperature, the inorganic near-infrared fluorescent material Mg(CrK) is obtained. 0.01 Ti 0.99 O3, which is in powder state.
[0096] Comparative Example 1
[0097] This comparative example provides a method for preparing an inorganic near-infrared fluorescent material, comprising the following steps:
[0098] According to MgCr 0.01 Ti 0.99 The stoichiometric ratio of each element in O3, magnesium oxide, titanium dioxide, and chromium trioxide are added to an agate mortar, and then an appropriate amount of anhydrous ethanol is added and ground for 30 minutes to obtain a first mixture;
[0099] The first mixture was transferred into a corundum crucible and placed into a muffle furnace for pre-calcination at 900° C. for 3 hours. After cooling to room temperature, an appropriate amount of anhydrous ethanol was added to the pre-calcined product and ground for 30 minutes to obtain a second mixture.
[0100] The second mixture is placed in a muffle furnace and sintered at 1300° C. for 2 hours (i.e., secondary sintering), and after cooling to room temperature, the inorganic near-infrared fluorescent material MgCr 0.01 Ti 0.99 O3, which is in powder state.
[0101] test:
[0102] (1) The crystal structure of the inorganic near-infrared fluorescent material prepared in Example 3 is shown in FIG. Figure 1 As shown by Figure 1 It can be seen that Mg 2+ and Ti 4+ Arranged in layers, each Mg 2+ and Ti 4+ Both with 6 O 2- Combined to form a distorted octahedral structure, while Cr 3+ and Na + Then replace Ti 4+ The crystal structure diagram of the inorganic near-infrared fluorescent material prepared in the other embodiments is the same as that of the inorganic near-infrared fluorescent material in Example 3.
[0103] (2) The inorganic near-infrared fluorescent materials prepared in Examples 1 to 8 were subjected to powder X-ray diffraction (XRD) testing. The XRD pattern of the inorganic near-infrared fluorescent material prepared in Example 3 is as follows: Figure 2 As shown (the XRD spectra of the inorganic near-infrared fluorescent materials prepared in the other embodiments are basically the same), which is very similar to the XRD spectrum obtained by crystal structure fitting, indicating that the inorganic near-infrared fluorescent material prepared in Example 3 is pure phase and does not need further purification.
[0104] (3) The inorganic near-infrared fluorescent material prepared in Example 3 was subjected to an energy spectrum test. The distribution diagram of each element is shown in FIG. Figure 3 As shown, it can be confirmed that it contains Mg, Ti, O, Cr and Na elements.
[0105] (4) The inorganic near-infrared fluorescent material prepared in Example 3 was subjected to an X-ray photoelectron spectroscopy (XPS) test. The results are as follows: Figure 4 As shown, it has Mg 1s peak, Na 1s peak, Cr 2p peak, O 1s peak, and Ti 2p peak.
[0106] (5) The fluorescence excitation spectra of the inorganic near-infrared fluorescent materials prepared in Example 3, Example 7, Example 8 and Comparative Example 1 were tested. The results are as follows: Figure 5 As shown, it can be seen that the inorganic near-infrared fluorescent materials prepared in Example 3, Example 7, and Example 8 have three fluorescence excitation peaks, which are located at 315nm, 514nm, and 728nm, respectively, and the excitation band covers ultraviolet and visible light. Compared with the inorganic near-infrared fluorescent material prepared in Comparative Example 1, the inorganic near-infrared fluorescent materials prepared in Example 3, Example 7, and Example 8 have stronger ultraviolet and red light absorption.
[0107] (6) The fluorescence emission spectra of the inorganic near-infrared fluorescent materials prepared in Example 3 and Comparative Example 1 were tested (excitation wavelength was 315 nm). The results are as follows: Figure 6 As shown, the fluorescence emission peak of the inorganic near-infrared fluorescent material prepared in Example 3 is located at 866 nm, and the emission wavelength band is 750-1200 nm, having a very wide emission range.
[0108] In addition, after calculation, the photoluminescence quantum yield of the inorganic near-infrared fluorescent material prepared in Example 3 is 31.55% (when the excitation wavelength is 520nm), which reaches the standard of commercial inorganic near-infrared fluorescent powder, indicating that the inorganic near-infrared fluorescent material provided by the present invention has commercial potential. Compared with the inorganic near-infrared fluorescent material prepared in Example 3, the fluorescence emission peak intensity of the inorganic near-infrared fluorescent material prepared in Comparative Example 1 is lower.
[0109] (7) The fluorescence emission spectra of the inorganic near-infrared fluorescent materials prepared in Example 3 and Comparative Example 1 were tested (excitation wavelength was 728 nm). The results are as follows: Figure 7 As shown, the fluorescence emission band of the inorganic near-infrared fluorescent material prepared in Example 3 is 750-1200nm, which has a very wide emission range. In addition, compared with the inorganic near-infrared fluorescent material prepared in Example 3, the fluorescence emission peak intensity of the inorganic near-infrared fluorescent material in Comparative Example 1 is lower.
[0110] In summary, the present invention provides an inorganic near-infrared fluorescent material and a preparation method and application thereof. The inorganic near-infrared fluorescent material has excellent near-infrared luminescence performance under the excitation of ultraviolet-visible light (315nm, 514nm, 728nm), a wide emission band range (750-1200nm), a peak position at 866nm, and a photoluminescence quantum yield of 31.55%, which meets commercial standards and can be applied to fields such as near-infrared imaging.
[0111] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. An inorganic near-infrared fluorescent material, characterized in that: The chemical formula of the inorganic near-infrared fluorescent material is Mg(CrM) x Ti 1-x O3; where 0 < x ≤ 0.06, and M is at least one alkali metal.
2. The inorganic near-infrared fluorescent material according to claim 1, characterized in that: M is at least one of Li, Na, and K.
3. A method for preparing the inorganic near-infrared fluorescent material according to claim 1, characterized in that: The steps include: According to Mg(CrM) x Ti 1-x The stoichiometric ratio of each element in O3 is obtained by mixing a magnesium source, a titanium source, a chromium source and an excess of at least one alkali metal source, sintering at a first preset temperature for a first preset time, and then sintering at a second preset temperature for a second preset time to obtain the inorganic near-infrared fluorescent material.
4. The preparation method according to claim 3, characterized in that: The preparation method of the inorganic near-infrared fluorescent material specifically comprises the following steps: According to Mg(CrM) x Ti 1-x The magnesium source, the titanium source, the chromium source and an excess of at least one alkali metal source are mixed in a stoichiometric ratio of each element in O3, and then subjected to a first grinding to obtain a first mixture; sintering the first mixture at a first preset temperature for a first preset time, and then grinding it for a second time to obtain a second mixture; The second mixture is sintered at a second preset temperature for a second preset time to obtain the inorganic near-infrared fluorescent material.
5. The preparation method according to claim 4, characterized in that: During the first grinding, ethanol is added, and the time of the first grinding is 15 to 30 minutes. During the second grinding, ethanol is added, and the time of the second grinding is 15 to 30 minutes.
6. The preparation method according to claim 3 or 4, characterized in that: The magnesium source includes magnesium oxide; the titanium source includes titanium dioxide; and the chromium source includes chromium trioxide.
7. The preparation method according to claim 3 or 4, characterized in that: The alkali metal source includes lithium carbonate, sodium carbonate or potassium carbonate.
8. The preparation method according to claim 3 or 4, characterized in that: The first preset temperature is 900° C., and the first preset time is 3 hours.
9. The preparation method according to claim 3 or 4, characterized in that: The second preset temperature is 1300° C., and the second preset time is 2 hours.
10. Use of the inorganic near-infrared fluorescent material according to any one of claims 1 to 2, or the inorganic near-infrared fluorescent material prepared by the preparation method according to any one of claims 3 to 9 in the field of near-infrared imaging.
Citation Information
Patent Citations
Chromium-thulium co-doped blue-violet light-to-narrow-spectrum near-infrared fluorescent material as well as preparation and application thereof
CN115772403A